SAHABAT OSIS: Penguatan Peran OSIS SMP dalam Pencegahan Bullying di Lingkungan Sekolah di Kabupaten Sidrap, Sulawesi Selatan: SAHABAT OSIS: Strengthening the Role of Junior High School Student Councils in Sidrap Regency in Preventing Bullying in Schools - Arini Enar Lestari AR; Muh. Adnan Kasogi S.; Novia Fridayanti; Rezky Ariany Aras; Andi Ahmad Hasan Tenriliweng; Hariashari Rahim (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The SAHABAT OSIS program is a strategic initiative aimed at strengthening the role of intra-school student organizations (OSIS) in preventing bullying in schools. This activity was conducted by Sociology Lecturers from Hasanuddin University as a form of community service targeting OSIS representatives from junior high schools across the Sidrap District. A total of 58 participants took part, comprising 30 students and 28 accompanying teachers. The methods used in this activity included lectures, interactive discussions, case studies, and Focus Group Discussions (FGD) between students and teachers. Evaluation results through pre-tests and post-tests showed an increase in the average knowledge score of participants from 8.11 ± 2.73 to 9.36 ± 1.30. This finding indicates that participants already had a good level of knowledge at the start, and that this intervention played a significant role in strengthening their understanding and social and ethical values, including digital ethics. The SAHABAT OSIS activity has proven to be effective and relevant to continue and expand as an effort to create a safe, inclusive, and violence-free school culture.